California League of Conservation Voters Press Release - Carl Pope::::::
This press release announces that the California League of Conservation Voters endorsed Jane Tolmach in the Democratic primary for the 36th Assembly District to succeed Ken McDonald. The organization praised her long-standing commitment to conservation issues in Ventura County, particularly her scrutiny of the proposed LNG terminal in Oxnard and her calls for federal hearings on safety concerns. It also commended her efforts on the Oxnard City Council to critically examine the economic, social, and environmental impacts of large city annexations, concluding that some were not in taxpayers' best interests. he release argues that Tolmach's persistent questioning and environmental vigilance would benefit voters and conservation efforts if she were elected to the Assembly.